People's Republic of China-Hong Kong Special Administrative Region : Financial Sector Assessment Program-Technical Note-Stress Testing the Banking Sector and Systemic Risk Analysis. (IMF Staff Country Reports; Country Report, 2021)
Hong Kong SAR (HKSAR) is a small and open economy, and a major international financial center with extensive linkages to Mainland China. Over the past two years, Hong Kong SAR's economy and financial sector were adversely impacted by domestic social unrest, US-China tensions, and the global COVID-19 pandemic, resulting in an unprecedented two consecutive years of negative economic growth.